Necrotizing Pancreatitis: A Review of Multidisciplinary Management - Sabo, Anthony; Goussous, Naeem; Sardana, Neeraj; Patel, Shirali; Cunningham, Steven C (JOP. Journal of the Pancreas, 2015)
The objective of this review is to summarize the current state of the art of the management of necrotizing pancreatitis, and to clarify some confusing points regarding the terminology and diagnosis of necrotizing pancreatitis, as these points are essential for management decisions and communication between providers and within the literature. Acute pancreatitis varies widely in its clinical presentation. Despite the publication of the Atlanta guidelines, misuse of pancreatitis terminology continues in the literature and in clinical practice, especially regarding the local complications associated with severe acute pancreatitis. Necrotizing pancreatitis is a manifestation of severe acute pancreatitis associated with significant morbidity and mortality. Diagnosis is aided by pancreas-protocol computed tomography or magnetic resonance imaging, ideally 72 h after onset of symptoms to achieve the most accurate characterization of pancreatic necrosis. The extent of necrosis correlates well with the incidence of infected necrosis, organ failure, need for debridement, and morbidity and mortality. Having established the diagnosis of pancreatic necrosis, goals of appropriately aggressive resuscitation should be established and adhered to in a multidisciplinary approach, ideally at a high-volume pancreatic center. The role of antibiotics is determined by the presence of infected necrosis. Early enteral feeds improve outcomes compared with parenteral nutrition. Pancreatic necrosis is associated with a multitude of complications which can lead to long-term morbidity or mortality. Interventional therapy should be guided by available resources and the principle of a minimally invasive approach. When open debridement is necessary, it should be delayed at least 3-6 weeks to allow demarcation of necrotic from viable tissue. Image: Suggested algorithm for the management of acute pancreatitis.